2000
DOI: 10.1177/070674370004500808
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Posttraumatic Stress Disorder in Adolescents with Conduct Disorder: Sex Differences and Onset Patterns

Abstract: Objective: To examine sex differences in the rate andsymptoms ofposttraumatic stress disorder (PTSD), trauma exposure, and onset patterns in youth with conduct disorder (CD).Method: Youth admitted to a clinicalfacility for severe behaviour problems completed the Diagnostic Interview for Children and Adolescents -Revised (DICA-R) . Studies demonstrate elevated rates of PTSD in delinquent adolescents and young adults, presumably because exposure to trauma potentiates both delinquent behaviour and PTSD. For ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Other studies of the mental health sequels following exposure to traumatic events have shown that both conduct problems and depression are common in trauma victims in addition to PTSD (Mazza & Reynolds, 1999;Reebye, Moretti, Wiebe, & Lessard, 2000;Yule et al, 2000). Further, remission of depression and conduct problems appears to be associated with remission of PTSD (Bolton, O'Ryan, .…”
Section: Traumatic Events and Mental Health Problems In Umamentioning
confidence: 99%
“…Other studies of the mental health sequels following exposure to traumatic events have shown that both conduct problems and depression are common in trauma victims in addition to PTSD (Mazza & Reynolds, 1999;Reebye, Moretti, Wiebe, & Lessard, 2000;Yule et al, 2000). Further, remission of depression and conduct problems appears to be associated with remission of PTSD (Bolton, O'Ryan, .…”
Section: Traumatic Events and Mental Health Problems In Umamentioning
confidence: 99%
“…Furthermore, the United Nation's Convention on the Rights of the Child states explicitly that children should be protected from any type of maltreatment, including physical punishment. Recent research efforts point to the fact that up to 17% of CD patients also fulfill criteria of posttraumatic stress disorder (PTSD) [33,34]. The role of trauma in the development of CD was reported in a retrospective study on men and women with life-time-persistent antisocial behavior that revealed a high rate of traumatic experience that was twice as high in the women's group (adjusted OR = 5.09) than in the male group (adjusted OR = 2.26) [2].…”
Section: Childhood Maltreatment and Potential For Violencementioning
confidence: 99%
“…Girls may tend to experience more of the type of trauma, especially sexual abuse or assault, most closely related to later PTSD symptoms. Boys, however, may be more likely to witness the death of a loved one than girls (Davis and Siegel 2000;De Bellis and Van Dillen 2005;Reebye et al 2000;Silva et al 2000;Tolin and Foa 2006;Walker et al 2004). Earlier age of report of physical, sexual, or multiple types of maltreatment is significantly related to later PTSD symptoms as well (English et al 2005;Pfefferbaum 2005).…”
Section: Ptsd and Maltreatment: Epidemiologymentioning
confidence: 99%